2021
DOI: 10.3390/nu13072335
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin Intake and Loss of Muscle Mass in Older People with Type 2 Diabetes: A Prospective Study of the KAMOGAWA-DM Cohort

Abstract: The aim of this prospective cohort study was to examine the relationships between the intakes of various vitamins and the loss of muscle mass in older people with type 2 diabetes (T2DM). The change in skeletal muscle mass index (SMI, kg/m2) (kg/m2/year) was defined as follows: (SMI at baseline (kg/m2) − SMI at follow-up (kg/m2))/follow-up period (year). The rate of SMI reduction (%) was calculated as follows (the change in SMI (kg/m2/year)/SMI at baseline (kg/m2)) × 100. The rate of SMI reduction ≥ 1.2% was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…In our study, vitamin A is related to handgrip strength in the total population but there was no association when analyzed by age group (three groups). Similar to our results, vitamin A levels have not been associated with a loss of muscle mass in the elderly with type 2 diabetes mellitus [ 29 ]. A relationship between vitamin A and muscle strength has not been established.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, vitamin A is related to handgrip strength in the total population but there was no association when analyzed by age group (three groups). Similar to our results, vitamin A levels have not been associated with a loss of muscle mass in the elderly with type 2 diabetes mellitus [ 29 ]. A relationship between vitamin A and muscle strength has not been established.…”
Section: Discussionsupporting
confidence: 91%
“…The number of outcomes was relatively small, further follow-up is imperative. Third, vitamin D status, including serum vitamin D level and vitamin D intake, did not assess in this study, although vitamin D status was reported to be associated with muscle mass loss (46) and muscle mass strength (47). Fourth, this study included only people with T2D; generalization to the other groups is hence uncertain.…”
Section: Discussionmentioning
confidence: 95%
“…Low levels of vitamin D have been observed to be related with muscle mass loss and enhanced sarcopenia [ 29 , 78 , 79 , 103 ]. Specifically, low levels of vitamin D are also related to reduced glycemic control, since vitamin D receptors located inside the pancreas and skeletal muscle contribute to glucose and muscle homeostasis [ 29 , 33 , 104 , 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is no significant association between diabetes and total dairy intake, although a high intake of milk may reduce T2DM risk among men [ 77 ]. In some studies, low levels of vitamin D have been observed to be related with muscle mass loss and sarcopenia [ 78 , 79 ]. However, the infusion of vitamin D in frail older patients did not show any significant result [ 72 ].…”
Section: Exercise and Diet To Control Sarcopenia And Type 2 Diabetes ...mentioning
confidence: 99%